Improving Urban Teachers’ Assessment Literacy through Synergistic Individualized Tutoring and Self-reflection - Dennis Murphy Odo (Networks: An Online Journal for Teacher Research, 2015)
In this reflective piece, I provide an account of one method I am developing for fostering the assessment literacy of pre-service teachers’ in an Master of Arts in Teaching program through individualized tutoring of K-6 learners that also incorporated collaborative reflection. This method was developed for a pre-service teacher education course on individualized literacy assessment and instruction. I incorporated the individualized tutoring sessions and candidate reflection activities to develop candidates’ assessment literacy in response to several observations I made as I taught the class. The teacher research I consulted to address this challenge echoed my experience of the general superficiality with which assessment is covered in teacher education programs (Popham, 2004, 2010; Stiggins, 1999). Consequently, teacher candidates are graduating with an inadequate grasp of key assessment concepts (e.g., validity, bias etc.) and low self-efficacy for using assessments (Volante & Fazio, 2007). In an effort to address this situation, I have integrated individualized tutoring and teacher reflection into the class. Scholars emphasize the benefit of teacher reflection for improving their understandings of instructional strategies, teaching challenges, and raising awareness of their own tacit beliefs (Brookfield, 1995) as well as the ability to integrate their growing knowledge into a coherent framework (Larrivee, 2000). Other researchers report that individualized tutoring can improve pre-service teachers’ instructional technique (Schwartz et al., 2009). The central aim of this paper is to reflect on my experience using tutoring and reflection activities to improve pre-service teachers’ understanding of key literacy assessment concepts, and their knowledge of administration and interpretation procedures for a variety of literacy assessment tools.